Large-Scale MIMO Transmitters for CR-NOMA in Fixed Physical Space: The Effect of Realistic System Impairments Using Stochastic Geometry - Emmanuel Ampoma Affum; Samuel Tweneboah-Koduah; Owusu Agyeman Antwi; Benjamin Asubam Weyori; Willie Ofosu (IEEE Open Journal of Vehicular Technology)
Hardware impairments (HWI) are imperfections in hardware components that diminish wireless communication performance. Unlike Geometric-based Stochastic Models (GBSMs), existing works on the impact of HWI on cooperative-relay (CR) Non-Orthogonal Multiple Access (NOMA) systems employ the Correlated-based Stochastic Model (CBSM), which does not capture realistic propagation mechanisms. Moreover, studies on CR-NOMA with large antenna transmitters (LATs) using CBSM and GBSM have attracted little attention in academia. We consider this as a computational issue. Although considerable work has been done, there is still a significant knowledge gap about how HWI and imperfect successive interference cancellation affect far-users in CR-NOMA with the LAT system. In this study, the LAT is considered a cylindrical array, and parameters such as delay spread, angle of arrival, and departure are incorporated to achieve a CR-NOMA-GBSM system with amplify-and-forward (AF) or decode-and-forward (DF) relaying schemes. To reduce computing demands, we offer a novel concept of using the physical dimensions of the array to derive the location vector of the antenna element. Using Monte Carlo simulation, near and far users' BER performances deteriorate for AF and DF at 15 dB and 5 dB or below, respectively. As far-users can receive comparable performances as near-users for both AF and DF in terms of achievable rates, this demonstrates the potential rewards of CR-NOMA with LAT.